EFFICACY OF VARIOUS SOURCES OF NUTRIENTS ON GROWTH, FLOWERING, YIELD AND QUALITY OF TOMATO (SOLANUM LYCOPERSICUM) CV. AZAD T-6 - A. PAL, S. MAJI,; GOVIND,; R. KUMAWAT,; S. KUMAR,; D. C. MEENA, (The Bioscan, 2015)
An investigation was carried out to assess the efficacy of various sources of nutrients on growth, fruiting, yield and quality of tomato cv. Azad T-6 at Babasaheb Bhimrao Ambedkar University, Lucknow during the year 2013-2014 under subtropical climate of Lucknow having high soil pH (8.2). Nine treatments comprising FYM, Vermicompost, Neemcake, PSB, Azotobacter and urea were applied following randomized block design with 3 replications. The study revealed that plant height (32.86 cm) and number of branches (8.83 per plant) at 90 days after transplanting (DAT) were maximum by the application of FYM 50% + Vermicompost 50% (T6). The treatment T6 also induced earliness in flowering as well as produced more flowers (36.42 per plant at full bloom) causing higher yield (84.33 total fruits per plant or 288.73 q per ha).The treatment T6 produced fruits with higher size (4.18 cm and 4.66 cm length and diameter, respectively) and pulp thickness, TSS: Acid ratio, vitamin C and sugars content. Thus, the study concluded that among the various sources of nutrients the application of FYM 50% + Vermicompost 50% (T6) was the best for improving growth, fruiting, fruit yield and quality of tomato cv. Azad T- 6 grown in Lucknow.